Seasonal Evolution of Supraglacial Lakes on Baltoro Glacier From 2016 to 2020 - Wendleder, Anna; Schmitt, Andreas; Erbertseder, Thilo; D’Angelo, Pablo; Mayer, Christoph; Braun, Matthias H. (Frontiers in Earth Science, 2021)
The existence of supraglacial lakes influences debris-covered glaciers in two ways. The absorption of solar radiation in the water leads to a higher ice ablation, and water draining through the glacier to its bed leads to a higher velocity. Rising air temperatures and changes in precipitation patterns provoke an increase in the supraglacial lakes in number and total area. However, the seasonal evolution of supraglacial lakes and thus their potential for influencing mass balance and ice dynamics have not yet been sufficiently analyzed. We present a summertime series of supraglacial lake evolution on Baltoro Glacier in the Karakoram from 2016 to 2020. The dense time series is enabled by a multi-sensor and multi-temporal approach based on optical (Sentinel-2 and PlanetScope) and Synthetic Aperture Radar (SAR; Sentinel-1 and TerraSAR-X) remote sensing data. The mapping of the seasonal lake evolution uses a semi-automatic approach, which includes a random forest classifier applied separately to each sensor. A combination of linear regression and the Hausdorff distance is used to harmonize between SAR- and optical-derived lake areas, producing consistent and internally robust time series dynamics. Seasonal variations in the lake area are linked with the Standardized Precipitation Index (SPI) and Standardized Temperature Index (STI) based on air temperature and precipitation data derived from the climate reanalysis dataset ERA5-Land. The largest aggregated lake area was found in 2018 with 5.783 km2, followed by 2019 with 4.703 km2, and 2020 with 4.606 km2. The years 2016 and 2017 showed the smallest areas with 3.606 and 3.653 km2, respectively. Our data suggest that warmer spring seasons (April–May) with higher precipitation rates lead to increased formation of supraglacial lakes. The time series decomposition shows a linear increase in the lake area of 11.12 ± 9.57% per year. Although the five-year observation period is too short to derive a significant trend, the tendency for a possible increase in the supraglacial lake area is in line with the pronounced positive anomalies of the SPI and STI during the observation period.